Luoghi di danza: Modernità, alienazione e mito dell’origine negli scritti giornalistici di Marco Ramperti - Taddeo, Giulia (Mimesis Journal, 2018)
Writer, journalist, theater and film critic, Marco Ramperti is one of the few that deals with dance in the Italian press of the fascist period. For the newspaper «La Stampa», between 1926 and 1928, he edits the column Luoghi di danza (dance venues), dedicated to ballroom and modern dances. The article investigates the performative nature of Ramperti’s writing, dominated by “staging” devices of the subject matter, as well as by an intrusive presence of the body, first of all that of the author. What emerges is an unprecedented image of the dance in the Twenties, at the same time catalysing the most alienating - and Pirandellian - aspects of modernity, but also a place where genuinely experiencing themselves and the others.